The principle of recognition and its role in converging between Islamic doctrines - ZIANI, Aissa; BIRAN , Benchaa (Social Empowerment Journal, 2020)
The project of convergence between Islamic doctrines is a serious attempt to maintain Islamic unity. Accordingly, it aimed at narrowing the differences between Islamic doctrines, which may help Islamic societies exceed doctrinal crises and move to address ethical problems. Yet, due to the lack of trust among Islamic doctrines, this paper demonstrates that the recognition principle is necessary to restore that trust. The results stressed Islamic societies should be immersed in some concepts, such as the concepts of recognition and citizenship. Thus, Islamic-Islamic dialogue activation and success depends on the ability of exceeding sectarianism and confessional ideas, and shift to the idea of citizenship, which promotes freedom of religious belief and coexistence.